Starting points in plant-bacteria nitrogen-fixing symbioses: intercellular invasion of the roots - Ibañez, Fernando Julio (2016)
Agricultural practices contribute to climate change by releasing greenhouse gases such as nitrous oxide that are mainly derived from nitrogen fertilizers. Therefore, understanding biological nitrogen fxation in farming systems is benefcial to agriculture and environmental preservation. In this context, a better grasp of nitrogen-fxing systems and nitrogen-fxing bacteria-plant associations will contribute to the optimization of these biological processes. Legumes and actinorhizal plants can engage in a symbiotic interaction with nitrogen-fxing rhizobia or actinomycetes, resulting in the formation of specialized root nodules. The legume-rhizobia interaction is mediated by a complex molecular signal exchange, where recognition of different bacterial determinants activates the nodulation program in the plant. To invade plants roots, bacteria follow different routes, which are determined by the host plant. Entrance via root hairs is probably the best understood. Alternatively, entry via intercellular invasion has been observed in many legumes. Although there are common features shared by intercellular infection mechanisms, differences are observed in the site of root invasion and bacterial spread on the cortex reaching and infecting a susceptible cell to form a nodule. This review focuses on intercellular bacterial invasion of roots observed in the Fabaceae and considers, within an evolutionary context, the different variants, distribution and molecular determinants involved. Intercellular invasion of actinorhizal plants and Parasponia is also discussed.